AWARENESS OF HEPATITIS IN PUBLIC ATTENDING PAEDIATRIC OUTDOOR AT ALLIED HOSPITAL FAISALABAD - Imran Sarwer; Shakil Ahmad; Nausheen Aslam (Journal of University Medical & Dental College, 2015)
ABSTRACT INTRODUCTION: Viral hepatitis is the most common liver disease and constitutes a worldwide problem. It is highly infectious. There is no speciﬁc treatment available for many cases in children and prevention is emphasized. OBJECTIVES: To know the level of awareness in people about different aspects of viral hepatitis in paediatric population. STUDY DESIGN: Descriptive, cross sectional study. PLACE AND DURATION OF STUDY: Study was conducted in outpatient department paediatrics at Allied Hospital Faisalabad during 06 months period from 01-07-2000 to 31-12-2000. METHODOLOGY: A total of one thousand attendants of children based on non probability consecutive sampling, were included in the study. Relevant information was obtained from parents and/or caregivers through simple questions in their own language. They were asked about hepatitis in respect of etiology, mode of spread, clinical features, complications, treatment, prognosis and prevention. RESULTS: Out of 1,000 respondents, 71% (n=710) were females, 41% (n=410) were illiterate and 78% (n=780) were from low socio-economic class. Mixed type of awareness was seen about hepatitis (Jaundice). 58 %( n=580) were of opinion that it is caused by hot weather or by taking some hot food. 74% (n=740) know about personal contact and 73% (n=730) had knowledge about contaminated syringes. Maximum awareness was seen about clinical features, 97% (n=970) people knew about yellowish discoloration of eyes, 88% (n=880) people were aware about yellowish discoloration of stool or urine. Regarding treatment 47% (n=470) people had concept about drug treatment by doctors, 42% (n=420) favoured Hakeems and 12% (n=120) preferred folk healers, only 09% (n=90) told about no treatment. 76% (n=760) knew that hepatitis can be prevented by avoiding contaminated food & water, 65% (n=650) were aware about syringes abuse, 61% (n=610) favoured Screening of blood transfusions and 57 % (n=570) preferred patient isolation. CONCLUSIONS: We conclude that there is partial awareness among parents/caregivers of children about various aspects of viral hepatitis in children especially its prevention. There is an urgent need for promoting awareness about the prevention of hepatitis in our society and Hepatitis awareness campaigns need to target people with less or no education, and limited access to media.